Penerapan etika bisnis Islam dalam strategi pemasaran syariah - Sri Winarsih; Muhammad Iqbal Fasa (PT. Intelek Cendikiawan Nusantara, 2024)
The application of Islamic business ethics in sharia marketing strategies is a crucial element that must be considered by business actors to achieve sustainability and build consumer trust. Islamic business ethics focuses on the principles of justice, transparency and social responsibility, which are in line with sharia values. Meanwhile, marketing strategy is a planned and systematic method for achieving company goals. This research discusses how the application of Islamic business ethics can increase the effectiveness of sharia marketing strategies, with an emphasis on product development, marketing communications, and relationships with consumers. The method used in this research is qualitative with a descriptive approach. The research results show that the application of Islamic business ethics not only improves the company's image, but also contributes to customer loyalty and sustainable business growth. Therefore, the integration of Islamic business ethics in sharia marketing strategies is the key to achieving business goals that are in accordance with sharia principles and modern market needs.